Enablers and barriers of social inclusion for young adults with intellectual disability: A multidimensional view*. Issue Volume 40:Issue1(2015) (2nd January 2015) - Van Asselt, Danae; Buchanan, Angus; Peterson, Sunila
Abstract: Background Factors that enhance the social exclusion and limit the social inclusion of adults with intellectual disability undermine their health and wellbeing. Thus it is important to reduce the impact of such factors. This may be achieved by deepening the understanding of the enablers and barriers to social inclusion, which were explored in this study using a multidimensional framework (O'Brien, J. (1989). What's worth working for? Leadership for better quality human services . Lithonia, GA: Responsive Systems Associates. Retrieved from http://thechp.syr.edu/wp-content/uploads/2013/02/whatsw.pdf) and the reports of young adults with intellectual disability, and family members, who were involved in an inclusive community leisure program. Method Interview data from 4 young adults and a parent and a sister were (1) thematically analysed, and (2) the resulting thematic structure was further analysed for enablers and barriers to social inclusion using the multidimensional framework. General observations conducted by the researcher on most participants, which were member checked, were used to validate the information gathered in the interviews. Results Seven primary themes emerged from the initial thematic analysis. Further analyses of the initial thematic structure using the multidimensional framework revealed 24 enablers and 10 barriers to the social inclusion of young adults. Conclusion Social inclusion of the young adults was influenced by enablers and barriers appearing across multiple dimensions. Implications for best service practice with young adults and their families to enable movement toward social inclusion are discussed.